ANALISIS PENGARUH KEPEMIMPINAN KHARISMATIK TERHADAP USAHA EKSTRA BAWAHAN PADA PONDOK PESANTREN DI EKS KARESIDENAN SURAKARTA - Lukman Hakim; Sholikhah Nur Rokhmah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2004)
The research examined the impact charismatic leadership with the setting of religious, educationalinstitution namely the Islamic boarding house more popularly known as the pondok pesantren inSurakarta residency. It was really to re-examine the research once conducted by Behling Mc Fillen(1996) using organizational commitment called “a Syncretical Model”. It was also related to thatconducted by Bass (1990) as a dependent variable. The objective was to analyze whether the variable ofbehavioral attributes model of charismatic leadership consisting of displays empathy, dramatizes themission, projects self- assurances, enhances the leader’s image, assures follower of their competency andprovides followers with opportunities to experience success and significantly affecting the follower extraeffort. The result of regression analysis by using the instrument called the program SPSS of tenthversion showed that displays empathy, projects self assurances, and enhances the leader’ image, andsignificantly affecting the follower’s extra efforts. Whereas the behaviors such as dramatizes the mission,assures followers of competency and provides opportunities to experience success had no significantinfluence toward the followers’ extra effort.